Propionibacterium acnes Accelerates Intervertebral Disc Degeneration by Inducing Pyroptosis of Nucleus Pulposus Cells via the ROS-NLRP3 Pathway. (1st February 2021) - Tang, Guoqing; Han, Xiaoguang; Lin, Zhijie; Qian, Hongbin; Chen, Bing; Zhou, Chengliang; Chen, Yong; Jiang, Weimin
Abstract : Our previous study verified the occurrence of Propionibacterium acnes ( P . acnes ), a low-virulence anaerobic bacterium, latently residing in degenerated intervertebral discs (IVDs), and the infection had a strong association with IVD degeneration. We explored whether P . acnes induces nucleus pulposus cell (NPC) pyroptosis, a more dangerous cell death process than apoptosis, and accelerates IVD degeneration via the pyroptotic products interleukin- (IL-) 1 β and IL-18. After coculturing with P . acnes, human NPCs showed significant upregulation of NOD-like receptor 3 (NLRP3), cleaved IL-1 β, cleaved caspase-1, and cleaved gasdermin D in response to the overexpression of IL-1 β and IL-18 in a time- and dose-dependent manner. In addition, the gene expression of inflammatory factors and catabolic enzymes significantly increased in normal NPCs when cocultured with pyroptotic NPCs in a transwell system, and the adverse effects were inhibited when NPC pyroptosis was suppressed. Furthermore, inoculation of P . acnes into the IVDs of rats caused significant pyroptosis of NPCs and remarkable IVD degeneration. Finally, coculture of NPCs with P . acnes induced the overexpression of reactive oxygen species (ROS) and NLRP3, while inhibition of both factors reduced NPC pyroptosis. Therefore, P . acnes induces NPC pyroptosis via the ROS-NLRP3 signaling pathway, and the pyroptotic NPCs cause an IVD degeneration cascade. Targeting the P . acnes -induced pyroptosis of NPCs may become an alternative treatment strategy for IVD degeneration in the future.